Menumbuhkan Literasi Anak Di Era Digital Berbasis Komunitas Di Komunitas Peduli Membaca (KOMPIM) Melalui Lomba Dedongengan Desa Ngemplak Kidul Kec. Margoyoso Kab. Pati - Khoiriyah, Nur; Kurniawan, Fajar Adhi; Setiawan, Aris; Shofiyullah, Shofiyullah (Community Development: Jurnal Pengembangan Masyarakat Islam, 2022)
Child literacy is a big challenge for the world of education today. This is influenced by various reasons including the increasingly widespread negative effects of digital, and the effects of online learning during Covid-19. The school environment, family and the surrounding community have a big contribution in improving children's literacy. The Dedongengan Competition activity is one of the efforts to foster community-based children's literacy in Ngemplak Kidul Village, Margoyoso District, Pati Regency. This activity was carried out using the PLA (Participatory Learning and Action) method. by using the PLA method various parties can participate in the implementation of this activity. With this method the participation of various parties was successfully carried out. Various partners include KOMPIM, local village government, local educational institutions, PMII Mutamakin Commissariat, KPI Study Program, and PIAUD Study Program. This dedongengan contest was successfully carried out with 11 children participating, and enthusiastically from partner institutions. Contest participants convey local wisdom fairy tales using attractive costumes. It is hoped that this activity can be continued continuously by the local community